Analysis of Emotional Intelligence Level of Class IX Students of SMP Negeri 1 Dukuhseti, Pati Regency - Kholisotin Mu'arofah; M.Th. S. R. Retnaningdyastuti; Padmi Dyah Yulianti (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2021)
Emotional intelligence is the ability of a person to know himself better and to know others so that he is able to establish harmonious relationships with others. Students who have high emotionality will be able to overcome the various problems they face and achieve success. This research uses quantitative research and is analyzed using descriptive research method with sample t-test technique tryout used. One variable in this research is emotional intelligence. The population in this study is 68 students. The sample of this research uses a random sampling method). with a specific purpose. The sample is taken as many as 68 students. The data collection uses a Likert scale. The data analysis method is assisted by using the SPSS (Statistical Product and Service Solution) program. A total of 12 students or 17.65%, have a low level of emotional intelligence, as many as 30 students or 44.12% have a moderate level of emotional intelligence, as many as 24 students or 35.29% have a high level of emotional intelligence and as many as 2 students or 2.94% have a very high level of emotional intelligence. At the moderate level is k the fact that knowledge of emotional intelligence is still rarely provided by formal education in improving students' emotional intelligence abilities.